(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article provides a comprehensive overview of diseases affecting root crops, including their impact, identification, prevention, and management strategies. Through literature analysis and discussion of methods, results, and conclusions, this article aims to enhance understanding and promote effective disease management in root crop cultivation.